Konsep Himpunan dalam Matematika: Definisi, Penyajian, Jenis, dan Sifat Operasi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This article explores the concept of sets in mathematics, a fundamental foundation for various disciplines. The discussion includes the definition of a set as a well-defined collection of objects, as well as various methods of presenting them such as enumeration, description of properties, set-forming notation, and Venn diagrams. In addition, the article outlines the various types of sets (empty, universe, equal, part, disjoint, crossed, equivalent, power) and explains the fundamental properties of set operations (identity, dominance, complement, idempotent, absorption, commutative, associative, distributive, De Morgan). The primary objective is to provide a concise yet comprehensive understanding of sets as a foundational pillar of logical and mathematical thinking.